2x = k
k = 22- 8√7
k - 22 = -8√7
(k-22)² = (-8√7)
k² - 44k + 484 = 448
k² - 44k = 448-484
k² - 44k = -36
k³ - 44k² = -36k
k³ - 44k² + 36k = 0
k³ - 49k² +5k² + 8k + 28k = 0
k³ + 5k² + 8k = 49k² - 28k
k³ + 4k² + k² + 4k + 4k = 49k² - 28k
k³ + 4k² + k² + 4k + 4k + 4 - 4 = 49k² - 28k
k³ + 4k² + k² + 4k + 4k + 4 = 49k² - 28k + 4
k³ + 4k² + k² + 4k + 4k + 4 = (7k - 2)²
(1+k)(k² + 4k + 4) = (7k - 2)²
(1+k)(k + 2)² = (7k - 2)²
(1+k) = (7k-2)²/(k+2)²
(1 + 2sinxcosx) = (7k-2)²/(k+2)²
(sin²x + cos²x + 2sinxcosx) = (7k-2)²/(k+2)²
(sinx + cosx)² = (7k-2)²/(k+2)²
(sinx + cosx) = (7k-2)/(k+2)
sinx + cosx = (7k -2)/k / (k+2)/k)
sinx + cosx = (7 - 2/k) / (1+2/k)
(sinx + cosx) (1 + 2/k) = 7 - 2/k
sinx + cosx + 2sinx/k + 2cosx/k = 7 - 2/k
sinx + cosx + 2/k(sinx + cosx) + 2/k = 7
sinx + cosx + 2/k(sinx + cosx + 1) = 7
sinx + cosx + 2/k(sinx + cosx + sin²x + cos²x) = 7
sinx + cosx + 2/2sinxcos (sinx + cosx + sin²x + cos²x) = 7
sinx + cosx + 1/cosx + 1/sinx + sinx/cosx + cosx/sinx = 7
sinx+cosx+secx+cosecx+tanx+cotx = 7
sinx + cosx + secx + cosecx + tanx + cotx = 7
3(sinx + cosx + secx + cosecx + tanx + cotx) = 21